Kwestia mniejszości węgierskiej w Czechosłowacji, Rumunii i Jugosławii okresie międzywojennym na łamach „Spraw Narodowościowych” (1927–1939) - Sylburska, Aleksandra (Acta Universitatis Lodziensis. Folia Historica, 2014)
In Polish historiography much less attention is paid to the influence of Hungarian minorities in successive countries on development of situation in Central-Eastern Europe during the interwar period than to the German ones. Such an attitude is mistaken because Hungarians took an active part in the revision of decisions taken during the Peace Conference in Paris. One of the reasons may be the language barrier because Hungarian is not widely spoken. However, as a considerably worthy source to history of national and ethnic problems in the interwar period, it is needed to recommend „Sprawy Narodowościowe” („Nationality Questions”), a periodical which was published from 1927 to 1939 by Institute of Nationality Questions Research in Warsaw. The read of this periodical delivers plenty of information about activity of Hungarian state and its minority representatives in the League of Nations, Union of International Associations of League of Nations, Interparliamentary Union and Congresses of Minorities in Geneva. There is also a number of articles about the situation of Hungarians living in Czechoslovakia, Romania and Yugoslavia, considering i. a. the minority law, political activity of Hungarian society, discrimination of governments towards this national group. „Sprawy Narodowościowe” allows draw some conclusions about the attitude of Hungarian regime to the role, which its minorities were to play in revision of decisions of Trianon Treaty and effectiveness of different interwar organizations which main goal was to guarantee the peace.